2006
DOI: 10.1158/1078-0432.ccr-06-0074
|View full text |Cite
|
Sign up to set email alerts
|

The Chemokine CCL5 as a Potential Prognostic Factor Predicting Disease Progression in Stage II Breast Cancer Patients

Abstract: Purpose: The aim of this study was to determine the prognostic value of the chemokine CCL5, considered as a promalignancy factor in breast cancer, in predicting breast cancer progression and to evaluate its ability to strengthen the prognostic significance of other biomarkers. Experimental Design: The expression of CCL5, alone and in conjunction with estrogen receptor (ER)-α, ER-β, progesterone receptor (PR), and HER-2/neu (ErbB2), was determined in breast tumor cells by immunohistochemistry. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
81
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(91 citation statements)
references
References 27 publications
9
81
0
1
Order By: Relevance
“…Conversely, the combinations of CCL5-negative/ER-a-positive and CCL5-negative/PR-positive in the stage II group as a whole were strongly correlative with an improved prognosis. 33 Furthermore, concomitant expression of the CCL5 and MCP-1 was observed in advanced human BC, 34 suggesting tumor-promoting interactions between these two chemokines. By immunohistochemistry analysis for the expression of CCL2, CCL5, IL-1b and TNF-a, Soria et al examined four groups of patients diagnosed with (i) benign breast disorders; (ii) ductal carcinoma in situ; (iii) invasive ducal carcinoma (IDC) without relapse; and (iv) IDC with relapse, respectively.…”
Section: Ccl5 and Human Breast Cancer (Bc)mentioning
confidence: 99%
“…Conversely, the combinations of CCL5-negative/ER-a-positive and CCL5-negative/PR-positive in the stage II group as a whole were strongly correlative with an improved prognosis. 33 Furthermore, concomitant expression of the CCL5 and MCP-1 was observed in advanced human BC, 34 suggesting tumor-promoting interactions between these two chemokines. By immunohistochemistry analysis for the expression of CCL2, CCL5, IL-1b and TNF-a, Soria et al examined four groups of patients diagnosed with (i) benign breast disorders; (ii) ductal carcinoma in situ; (iii) invasive ducal carcinoma (IDC) without relapse; and (iv) IDC with relapse, respectively.…”
Section: Ccl5 and Human Breast Cancer (Bc)mentioning
confidence: 99%
“…In addition to changes in myeloid cells, there were higher frequencies in the more mature population of blasts and progenitors in KO mice. Previous studies by others have mostly focused on tumor-derived CCL5, and found overexpression of CCL5 in advanced stages of breast cancer [5]. In more recent years, mesenchymal stem cell-derived CCL5 has been shown to contribute to cancer cell motility, invasion and metastasis [49,50].…”
Section: Yan Zhang Et Al 405mentioning
confidence: 99%
“…Tumor-derived CCL5 is detected in many clinical specimens of breast and cervical cancers; greater plasma levels in patients with progressive and more advanced disease than those in remission [5][6][7], and it constitutes a prominent part of a poor prognosis signature of inflammatory breast cancer [8,9]. The concentration of CCL5 was significantly higher in the groups of patients with or without axillary lymph node metastasis [10].…”
Section: Introductionmentioning
confidence: 99%
“…CCL5 has also been shown to be a significant predictor of progression in patients with stage II breast cancer (Hahoshen et al 2006). In another study, tumors that expressed higher levels of CCL5 were more likely to metastasize in comparison with tumors that did not express as much CCL5 (Stormes et al 2005).…”
Section: To the Editormentioning
confidence: 95%